Evaluation of humic substances during co-composting of sewage sludge and corn stalk under different aeration rates. (December 2017) - Li, Shuyan; Li, Danyang; Li, Jijin; Li, Guoxue; Zhang, Bangxi
Highlights: Influence of aeration rate (AR) on humification was revealed. AR with 0.24 L·kg −1 DM min −1 accelerated humification and maturity process. The decrease of C/N and H/C atom ratio in HA reflects compost stability. AR significantly influenced the HA/FA ratio during co-compost with sewage sludge. Abstract: Sewage sludge and corn stalk were co-composted under different aeration rates 0.12 (AR0.12), 0.24 (AR0.24), 0.36 (AR0.36) L·kg −1  DM min −1, respectively. Transformation of humic substance was evaluated by a series of chemical and spectroscopic methods to reveal compost humification. Results showed that aeration rate could significantly affect compost stability and humification process. Humic acid contents in AR0.24 were significantly higher than those in the other two treatments. The final humic acid/fulvic acid ratios in AR0.12, AR0.24 and AR0.36 treatment were 1.0, 1.9 and 0.8, respectively, corresponding to the final E4 /E6 of 4.7, 3.2 and 5.5. Moreover, compost in AR0.24 treatment had a high stability degree due to the low C/N atom ratio and high C/H atom ratio. However, it is noteworthy that composting could not significantly affect the structure of HA in a 35-day period. These results indicate that composting with the aeration rate of 0.24 L·kg −1  DM min −1 could accelerated the humification process.